Respuestas
Respuesta dada por:
1
Reemplaza los puntos para despejar las constantes
f(0) = 8
![b {a}^{0} = 8 \\ b = 8 b {a}^{0} = 8 \\ b = 8](https://tex.z-dn.net/?f=b+%7Ba%7D%5E%7B0%7D++%3D+8+%5C%5C+b+%3D+8)
Luego como b=8
![f(x) = 8 {a}^{x} f(x) = 8 {a}^{x}](https://tex.z-dn.net/?f=f%28x%29+%3D+8+%7Ba%7D%5E%7Bx%7D+)
Reemplazamos el segundo punto
f(3) = 1
![8 {a}^{3} = 1 \\ {a}^{3} = \frac{1}{8} \\ a \: = \sqrt[3]{ \frac{1}{8} } \\ a = \frac{1}{2} 8 {a}^{3} = 1 \\ {a}^{3} = \frac{1}{8} \\ a \: = \sqrt[3]{ \frac{1}{8} } \\ a = \frac{1}{2}](https://tex.z-dn.net/?f=+8+%7Ba%7D%5E%7B3%7D++%3D+1+%5C%5C++%7Ba%7D%5E%7B3%7D++%3D++%5Cfrac%7B1%7D%7B8%7D++%5C%5C+a+%5C%3A++%3D++%5Csqrt%5B3%5D%7B+%5Cfrac%7B1%7D%7B8%7D+%7D++%5C%5C+a+%3D++%5Cfrac%7B1%7D%7B2%7D+)
luego
![log_{b}(a) \\ = log_{8}( \frac{1}{2} ) \\ = log_{8}(1) - log_{8}(2) \\ = 0 - \frac{1}{3} \\ = - \frac{1}{3} log_{b}(a) \\ = log_{8}( \frac{1}{2} ) \\ = log_{8}(1) - log_{8}(2) \\ = 0 - \frac{1}{3} \\ = - \frac{1}{3}](https://tex.z-dn.net/?f=+log_%7Bb%7D%28a%29++%5C%5C+++%3D++log_%7B8%7D%28+%5Cfrac%7B1%7D%7B2%7D+%29++%5C%5C++%3D++log_%7B8%7D%281%29++-++log_%7B8%7D%282%29++%5C%5C++%3D+0+-++%5Cfrac%7B1%7D%7B3%7D++%5C%5C++%3D++-++%5Cfrac%7B1%7D%7B3%7D+)
f(0) = 8
Luego como b=8
Reemplazamos el segundo punto
f(3) = 1
luego
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años